An image of Brahma - Temples of India Project Team (Jio Institute, 2024)
The bhadra (central offset) positioned on the rear (east) wall of the garbhagriha garbhagriha (sanctum sanctorum) of the Undeshwar Temple features an image of Brahma. The deity, albeit significantly damaged, is depicted seated on a pedestal. He is portrayed with three faces and four arms, although his upper arms are broken. In his lower left hand, he holds a kamandalu (water pot) while displaying the Varada hasta (hand gesture of conferring a boon) gesture with his lower right hand. Brahma is adorned with a jatamukuta (crown of matted hair), a mustache, and a beard.